Entropy jump at the first-order vortex phase transition in Bi2Sr2CaCu2O8+δ with columnar defects - Rumi, G.; Albornoz, L.J.; Pedrazzini, P.; Dolz, M.I.; Pastoriza, H.; van der Beek, C.J.; Konczykowski, M.; Fasano, Y.; Fasano, Yanina; Pedrazzini, Pablo (Elsevier, 2019)
Fil: Rumi, G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina